Reachability Problems 5th International Workshop, RP 2011, Genoa, Italy, September 28-30, 2011. Proceedings - Delzanno, Giorgio; Potapov, Igor.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 5th International Workshop on Reachability Problems, RP 2011, held in Genoa, Italy, in September 2011. The 16 papers presented together with 4 invited talks were carefully reviewed and selected from 24 submissions. The workshop deals with reachability problems that appear in algebraic structures, computational models, hybrid systems, logic, and verification. Reachability is a fundamental problem that appears in several different contexts: finite- and infinite-state concurrent systems, computational models like cellular automata and Petri nets, decision procedures for classical, modal and temporal logic, program analysis, discrete and continuous systems, time critical systems, and open systems modelled as games.
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Logics and Meanings of Programs; Software Engineering; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices